Grit and Life Satisfaction Among College Students During the Recurrent Outbreak of COVID-19 in China: The Mediating Role of Depression and the Moderating Role of Stressful Life Events - Liu, Haidong; Yu, Zhijun; Ye, Baojuan; Yang, Qiang (Frontiers in Public Health, 2022)
The global recurrent outbreak of COVID-19 has brought immense psychological distress to those affected. We conducted this study to explore the relationship among grit, stressful life events, depression, and life satisfaction in college students during the recurrent outbreak of COVID-19. We investigated 888 college students from across China, with an average age of 20.84 (SD=1.57) years. Participants completed questionnaires regarding grit, depression, stressful life events, and life satisfaction. The results showed that 1) grit was correlated with life satisfaction; 2) depression mediated the relationship between grit and life satisfaction; 3) The relationship between grit and depression was moderated by stressful life events. The association between grit and depression became weaker for college students with high stressful life events. The results indicated that concerned about depression and stressful life events may be the main targets for improving life satisfaction among college students during the recurrent outbreak of COVID-19.